Adolescent endometriosis - Nanthakumar, Meenu P.; Arumugam, Sendhil C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Endometriosis is predominantly a disease of women of reproductive age group. Endometriosis is not uncommon in adolescents. Presentation tends to focus on pain, especially intractable dysmenorrhea and chronic pelvic pain. In around 60% of patients with endometriosis symptoms start in adolscence. Pain unresponsive to treatment is the usual indication for a Laproscopy. The appearance of endometriotic lesions is different from that of adults. Medical and surgical options for treatment are available. Endometriosis may be progressive and adverse effects may go beyond pain and cause infertility.